A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

A balanced approach to the potential of octopus aquaculture - Ian G. Gleadall; Roger Villanueva; Gregory J. Barord; Zoe Doubleday; Felipe Aguado-Giménez; Nobuhiko Akiyama; Eduardo Almansa; Cheryl L. Ames; Alexander Arkhipkin; Otilio Avendaño; Chris Barrett; Giambattista Bello; et al. (Marine Policy, 2025)

Corrigendum to “Large sardine resource discovered off south-eastern Australia: Potential risks, challenges and benefits of establishing a new fishery” [Mar. Policy 155 (2023) 105739] - Tim M. Ward; Barrett W. Wolfe; Gretchen L. Grammer; Alex R. Ivey; Edward King; Andreas Schiller; Karlie S. McDonald; Jeffrey M. Dambacher (Marine Policy, 2025)

Environmental and dietary factors associated with urinary OH-PAHs in mid-pregnancy in a large multi-site study - Anne M. Riederer; Allison R. Sherris; Adam A. Szpiro; Melissa M. Melough; Christopher D. Simpson; Christine T. Loftus; Drew B. Day; Erin R. Wallace; Leonardo Trasande; Emily S. Barrett; Ruby HN. Nguyen; Kurunthachalam Kannan; et al. (Environmental Research, 2025)

Large sardine resource discovered off south-eastern Australia: Potential risks, challenges and benefits of establishing a new fishery - Tim M. Ward; Barrett W. Wolfe; Gretchen L. Grammer; Alex R. Ivey; Edward King; Andreas Schiller; Karlie S. McDonald; Jeffrey M. Dambacher (Marine Policy, 2023)

Prenatal exposure to polycyclic aromatic hydrocarbons is not associated with behavior problems in preschool and early school-aged children: A prospective multi-cohort study - Erin R. Wallace; Erin Buth; Adam A. Szpiro; Yu Ni; Christine T. Loftus; Erin Masterson; Drew B. Day; Bob Z. Sun; Alexis Sullivan; Emily Barrett; Ruby HN. Nguyen; Morgan Robinson; et al. (Environmental Research, 2023)

Characteristics of extreme daily precipitation events over the Canadian Arctic - Mark C. Serreze; Jessica Voveris; Andrew P. Barrett; Shari Fox; Peter D. Blanken; Alex Crawford (International Journal of Climatology, 2022)
Given growing interest in extreme high‐latitude weather events, we use records from nine meteorological stations and atmospheric reanalysis data to examine extreme daily precipitation events (leading, 99th and 95th percentile) over Arctic Canada. Leading events span 90 mm at Cape Dyer, along the southeast coast of Baffin Island, to 26 mm at Sachs Harbour, on the southwest coast of Banks Island. The 95th percentiles range from 20 to 30% of leading event sizes. Extreme events are most common on or near the month of climatological peak precipitation. Contrasting with Eurasian continental sites having a July precipitation peak corresponding to the seasonal peak in precipitable water, seasonal cycles in precipitation and the frequency of extremes over Arctic Canada are more varied, reflecting marine influences. At Cape Dyer and Clyde River, mean precipitation and the frequency of extremes peak in October when the atmosphere is quickly cooling, promoting strong evaporation from Baffin Bay. At all stations, leading events involved snowfall and strong winds and were associated with cyclone passages (mostly of relatively strong storms). They also involved strong vapour fluxes, sometimes associated with atmospheric rivers or their remnants. The most unusual sequence of events identified here occurred at Clyde River, where the three largest recorded precipitation events occurred in April of 1977. Obtaining first‐hand accounts of this series of events has proven elusive. Identified links between extreme events and atmospheric rivers demonstrates the need to better understand how the characteristics of such features will change in the future.

Extreme daily precipitation events at Spitsbergen, an Arctic Island - Mark C. Serreze; Alex D. Crawford; Andrew P. Barrett (International Journal of Climatology, 2015)
Daily station records and output from the MERRA atmospheric reanalysis for the period 1979 onwards are used to examine extreme daily precipitation events at Ny Ålesund and three other sites located on Spitsbergen. Spitsbergen, lying between 77°N and 80°N, is the largest island of the Svalbard Archipelago. The region is frequently influenced by extratropical cyclones associated with the North Atlantic cyclone track and (in winter) regional baroclinicity due to proximity to the sea ice margin. Despite the stronger cyclone activity in winter, extreme precipitation events at Ny Ålesund, defined as those in the top 1% of the statistical distribution, can occur year round. On the basis of a composite analysis, extreme events tend to occur when the region is influenced by a trough of low sea level pressure extending from the southwest, southerly winds in the troposphere, positive anomalies in precipitable water, and pronounced upward motion (negative omega) at 500 hPa . This is linked to positive anomalies in 500 hPa heights over the Barents Sea and negative anomalies over Greenland. While individual extreme events do not share all of these characteristics, strong southerly flow and positive anomalies in precipitable water provide a near common thread. Reflecting local topography, extremes at Ny Ålesund are typically not well represented at other stations on the island, but there are notable exceptions. Some of the largest precipitation events can be associated with features resembling ‘atmospheric rivers’, seen as narrow corridors of pronounced positive anomalies in precipitable water extending thousands of kilometres south into the subtropical Atlantic. There is no systematic pattern of temporal trends in the frequency or magnitude of extremes.

Consulting Forestry / Certification and Ecosystem Services - James Coufal; Carl Wiedemann; Jacob Gorman; Larry Teeter; Yaoqi Zhang; Michael Kilgore; Kristell Miller; Stephanie Snyder; Sun Chang; Miriam Davis; Stanley Asah; J. Mark Fly; et al. (Journal of Forestry, 2011)
45The industrialization of the United States throughout the 19th century resulted in the exploitation of millions of acres of timberland across the country. Logging during that era was described by critics as “cut out and get out” because the land was usually abandoned after the merchantable timber was exhausted. Concern about future timber supplies and the effect of logging on watersheds spurred the development of professional forestry after the Civil War. The first forestry leaders, including Bernhard Fernow and Gifford Pinchot, encouraged private non-industrial forest owners to sustainably manage their woodlands and specifically warned against destructive logging practices—including “cutting the best and leaving the rest”—aka high-grading. During the 1920s and 30s both the Forest Service and SAF spurred initiatives to encourage sustainable timber harvesting practices on private forestland. Although great progress has been made in forest management, logging on most private non-industrial forest land in the east has not changed significantly since the 19th century. Landowners usually sell timber without using the services of a forester, allowing the buyer to selectively cut the most valuable trees in the woodlot. Although this can reduce future value by 70-90%, it remains common practice because both the landowner and the timber buyer maximize short term income. The timber value and productivity of millions of acres of woodland throughout the United States have been significantly degraded as a result. This paper will trace the history of high-grading as described by forestry leaders from the 19th century through the 21st and will show that much work remains unfinished.

Silviculture and Forest Ecology - David Mercker; Ryan Blair; Don Tyler; Theresa Jain; Russell Graham; Donald Rockwood; Nicholas Koch; Jeremy Brawner; Omar Carrero; Kristofer Covey; Alex Barrett; Mark Ashton; et al. (Journal of Forestry, 2011)
2Over the past several decades, federal incentive programs have encouraged the restoration of bottomland forests throughout the West Gulf Coastal Plain (WGCP) and the Lower Mississippi Alluvial Valley (LMAV). Programs such as the Conservation Reserve (CRP) and Wetlands Reserve (WRP) Programs have been marginally successful (Stanturf et al. 2001). Foresters and contractors often follow conventional tree planting procedures that are well established for upland sites, but prove problematic in bottomlands. High water tables, soil drainage and compaction, overland flooding and diverse soil properties make species selection difficult. Slight changes in topography and soil structure often have a dramatic effect on survival and growth of planted oak seedlings (Hodges and Schweitzer 1979). This project documented the survival and growth of six-year old seedlings that were established on a bottomland site in 2004, located at the West Tennessee Research and Education Center, Jackson, Tennessee. The purpose was to determine how soil drainage as indicated by mottling (specifically, the point of 50 percent gray color throughout the soil profile) affects the survival and growth of bottomland oak species. The findings suggest that practitioners plant Nuttall, pin and overcup oaks in poorly drained soils. As the drainage improves, begin mixing in willow oak. In the best drained soils (if they exist), finish by including water, swamp chestnut, swamp white, Shumard, cherrybark and bur oaks. Potential species diversity should expand as the soil drainage improves.